Development and analysis of a customer-demand-driven semiconductor supply chain model using the High Level Architecture. (6th March 2007) - Chong, Chin Soon; Lendermann, Peter; Gan, Boon Ping; Duarte, Brett M.; Fowler, John; Callarman, Thomas
Effective supply chain management (SCM) enables organisations to be more competitive in the current world of global manufacturing. Simulation can help by evaluating the feasibility of alternative policies and arrangements for managing a supply chain. However, detailed simulation of the supply chain can be complex and computationally intensive. We develop a distributed simulation model that can be used to study such a supply chain. We fine tune the execution speed of the model, and then use the model to investigate on how the frequency of inventory updates and demand changes affect the on-time-delivery (OTD) performance of the entire supply chain.